2023
DOI: 10.1039/d3ob00792h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, reactions and application of chalcones: a systematic review

Abstract: Chalcones are a group of naturally occurring compounds that have biological effects that include anti-inflammatory, anti-cancer, and antibacterial properties. Current chalcone research, including its synthesis, structure-activity connections, and biological activities,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 250 publications
0
11
0
Order By: Relevance
“…Elements analysis, mass, UV/VIS, magnetic susceptibility, molar conductance, and FT-IR were performed to characterize the structures of the novel complexes and to establish the chelation nature of the tetradentate O 2 N 2 donor of TM. [49][50][51] This has been confirmed by a DFT study that showed the possession of N and O to negative charges, in contrast to the sulfur atom of the thiazole ring, which has a positive charge, indicating that it is not involved in the chelation process. The analytical data (Table 1) quite closely match the proposed chemical structures.…”
Section: Characterization Of the Novel Complexesmentioning
confidence: 70%
“…Elements analysis, mass, UV/VIS, magnetic susceptibility, molar conductance, and FT-IR were performed to characterize the structures of the novel complexes and to establish the chelation nature of the tetradentate O 2 N 2 donor of TM. [49][50][51] This has been confirmed by a DFT study that showed the possession of N and O to negative charges, in contrast to the sulfur atom of the thiazole ring, which has a positive charge, indicating that it is not involved in the chelation process. The analytical data (Table 1) quite closely match the proposed chemical structures.…”
Section: Characterization Of the Novel Complexesmentioning
confidence: 70%
“…The Wnt signaling pathway is a complex pathway that regulates cell growth and proliferation 50 . The abnormal excitation of the pathway due to genetic mutation or increased stability can activate the abnormal expression of downstream target genes, including, c-Myc, Cyclin, and MMP-7, which can lead to cell proliferation, inhibition of cell apoptosis, and tumor formation 51 . Canonical Wnt/β-catenin pathway stimulates gene transcription through β-catenin 48 , 52 .…”
Section: Molecular Studiesmentioning
confidence: 99%
“…To demonstrate the antioxidant potential of the newly synthesized compounds (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), their radical-scavenging capacities were determined using the 2,2-diphenyl-1-picrylhydrazyl radical (DPPH) assay. [31] This method is based on the ability of the DPPH radical to abstract H-atoms from antioxidants (AÀ H) to form the hydrazine derivative DPPHÀ H Figure 1, as depicted in reaction 1.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…Chalcones, (E)-1,3-diaryl-2-propen-1-ones, have attracted much attention in the field of medicinal chemistry due to their facile synthesis, high reactivity, and promising pharmacological activities. [3,4] They represent a group of natural products that belong to the flavonoid family, and can exist in various flowers, fruits, vegetables. Several synthetic methods have been reported for the preparation of chalcones, such as Claisen-Schmidt reactions, Heck coupling, Suzuki-Miyaura coupling, and Witting reactions.…”
Section: Introductionmentioning
confidence: 99%